145 President Oral Presentation Pick: Prenatal stress increases skeletal muscle mitochondrial volume density and function in yearling Brahman calves. (30th November 2020) - Guy, Chloey P; Wellman, Catherine L; Riley, David G; Long, Charles R; Randel, Ron D; Welsh, Thomas H; White-Springer, Sarah H
Abstract: We previously determined that prenatal stress (PNS) differentially affected methylation of DNA from leukocytes of 28-d-old calves. Specifically, COX14 (cytochrome c oxidase (COX) assembly factor) and CKMT1B (mitochondrial creatine kinase U-type) were hypomethylated and COA5 (COX assembly factor 5), COX5A (COX subunit 5A), NRF1 (nuclear respiratory factor 1), and GSST1 (glutathione S-transferase theta-1) were hypermethylated in PNS compared to non-PNS calves (P ≤ 0.05). Our current objective was to test the hypothesis that PNS exhibit impaired mitochondrial function and greater oxidative stress than non-PNS calves. Blood and longissimus dorsi muscle samples were collected from yearling Brahman calves whose mothers were stressed by 2 h transportation at 60, 80, 100, 120, and 140 days of gestation (PNS; 8 bulls, 6 heifers) and non-PNS calves (4 bulls, 6 heifers). Serum was evaluated for the stress hormone, cortisol, and muscle damage marker, creatine kinase; muscle was analyzed for mitochondrial volume density and function by citrate synthase (CS) and COX activities, respectively, concentration of malondialdehyde, a lipid peroxidation marker, and activity of the antioxidant, superoxide dismutase (SOD). Data were analyzed using mixed linear models with treatment and sex as fixed effects. Serum cortisol was numerically higher in PNS than non-PNS calves but was not statistically different. Muscle CS and COX activities relative to protein were greater in PNS than non-PNS calves (P ≤ 0.03), but COX relative to CS activity was similar between groups. Activity of COX was greater in bulls than heifers (P = 0.03), but no other measure was affected by sex. All other measures were unaffected by PNS. Prenatal stress did not affect markers of muscle damage and oxidative stress in yearling Brahman calves at rest but mitochondrial volume density and function were greater in PNS calves. Acute stressors induce oxidative stress, so implications of differences in mitochondria in PNS calves following a stressor should be investigated.